Influence of pedalling with the metatarsus on running characteristics in triathlon competition - Illes,S.; Hassmann, M.; Hren, M.; Ilagan, R.; Litzenberger, S.; Sabo, A. (Procedia Engineering, 2010)
This study investigates a cyclist shoe cleat position change from conventional position below metatarsophalangeal joint to below metatarsus during cycling. The focus is the influence on a following running split with respect to running characteristics, such as the plantar pressure distribution. The goal is to find out significant tendencies which could lead to higher performance in running with athletes used to the metatarsal position. In addition, statistical analysis of metabolic parameters is included. Analysing 10 healthy subjects (age 24.75±2.25, height 177.10cm±3.63cm, weight 68.00kg±9.18kg, male=8, triathletes=3, cyclists=2) indicates that plantar pressure and running frequency after cycling in metatarsal position is more similar to running without previous cycling activity compared to the conventional position. Metabolic analysis shows lower power output with metatarsal pedalling because of being inexperienced to that pedalling technique.